IMPROVING 7A GRADERS’ VOCABULARY MASTERY THROUGH WHAT’S MISSING GAME AT SMP MUHASA MALANG - Riski Lestiono; Abdul Hafid (Erudio Journal of Educational Innovation, 2015)
This study employed classroom action research. The subjects of this study were 7A graders at SMP Muhammadiyah 1 Malang, in total of 30 students in class. Many students had low achievement in English, especially about the English vocabulary. In this case, the researchers used what’s missing game as a method to improve their vocabulary mastery. The object is to remember what object is missing when it is removed by the researcher. The findings revealed that in cycle I the implementation of what’s missing game was running well, although there were still students who got low score in vocabulary test. Meanwhile in cycle II, all 30 students passed the minimum criteria of completeness in vocabulary test. This cycle was declared successful because all students had reached the minimum criteria of completeness. Cycle I and II were conducted in eight meetings; each meeting had different subject to be discussed. The improvement of 7A graders’ vocabulary mastery was because of the change of strategies which were used by the researchers. In cycle I, students worked in pairs; but in cycle II, they worked in groups consisting of four to five members. Students were asked to observe and remember all vocabularies in cycle I; but in cycle II, they were asked to observe and memorize those words as well. Students had to pronounce the words together with their friends; but in cycle II, they were asked to pronounce those vocabularies one by one. Key words: Vocabulary mastery, Games, What’s missing game